Olive$1 (Bs ocean s - Henkes, Kevin (New York : Greenwillow Books, 2003)
On a summer visit to her grandmother$1 (Bs cottage by the ocean, twelve-year-old Martha gains perspective on the death of a classmate, on her relationship with her grandmother, on her feelings for an older boy, and on her plans to be a writer.s
Keywords: Grandmothers -- Fiction; Family life -- Fiction; Self-perception -- Fiction